Pengaruh Motivasi dan Disiplin Kerja terhadap Produktifitas Karyawan Hotel Rylich Panorama Kota Sorong - Renouw, Ade Andriani; Longkutoy, Meyta; Mambrasar, Novanti Novalinda (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract This study aims to analyze the Influence of Motivation and Work Discipline on Employee Productivity at Rylich Panorama Hotel, Sorong City. The data analysis method used is quantitative descriptive analysis. The results of the t-test, the independent variable partially, the t-value of Motivation has a positive/significant effect on the dependent variable, where the t-value of the Motivation variable is tcount 2.167> from ttable 1.6779, or the significance value is 0.000 less than 0.05. This means that because t-count> t-table, it can be concluded that the hypothesis (H1) is accepted, the Work Discipline variable is tcount 5.351> from ttable 1.6779, or the significance value is 0.000 less than 0.05. This means that the hypothesis (H2) is accepted. The results of the F test obtained an Fcount value of 37.106 with a significance of 0.000. indicating significance <0.05. means Motivation and Discipline simultaneously affect Employee Productivity at Rylich Panorama Hotel, Sorong City.